38. PITFALLS IN HISTOPATHOLOGICAL DIAGNOSIS OF SCLEROSING PNEUMOCYTOMA ON SMALL BIOPSY AND FROZEN SECTION SPECIMENS: PRACTICAL EXPERIENCE AT PATHOLOGY DEPARTMENT, NATIONAL LUNG HOSPITAL FROM 2021 TO 2023 (Vietnam Journal of Community Medicine, 2024)
Background: National Lung Hospital is a leading hospital specializing in respiratory diseases and thoracic surgery in Vietnam. The opportunity to access the diagnosis of lung nodules such as sclerosing pneumocytoma (SP) is quite common. This is a rare benign tumor in the lung. The tumor originates from pneumocyte and its histopathological features also create many pitfalls that are easily confused with highly differentiated adenocarcinoma.Objective: To share experiences in histopathological diagnosis to avoid pitfalls when diagnosing sclerosing pneumocytoma at the Pathology Department – National Lung Hospital from 2021 to 2023, especially small biopsies and frozen section specimens.Results: Report of 3 cases of sclerosing pneumothorax that were operated on at the National Lung Hospital with distinguishing features in clinical, imaging, small biopsy histology or frozen section specimens, differentiated from adenocarcinoma.Conclusion: With SP, clinical symptoms and imaging diagnoses are non-specific, and diverse histopathological morphology will create challenges when diagnosing, with the risk of confusion with consolidation lesions or malignant tumors, lead to errors in treatment and prognosis. The physians need to accumulate knowledge and practice experience to avoid these pitfalls.
Keywords: Lung adenoma; Sclerosing Pneumocytoma; Pitfalls in diagnosing sclerosing pneumocytoma, diagnosing lung nodules.